PENGARUH KOMPENSASI, MOTIVASI, DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DIVISI SALES DI HONDA DENPASAR AGUNG - Santoni, Ni Putu Cindyana Claudia; Suana, I Wayan (E-Jurnal Manajemen, 2018)
The purpose of this study was to determine the effect of compensation, motivation, and discipline on work productivity. This research was conducted in companies engaged in the automotive trade industry is Honda Denpasar Court. The total sample of 40 people. Data were collected through interviews and questionnaires as well as using multiple linear regression analysis. Based on the analysis found that compensation is positive and significant effect on work productivity. Motivation has a significant positive pegaruh to work productivity. Labor discipline and significant positive effect on work productivity. A good compensation is believed to encourage employees to be willing to work more productively. Motivation will increase the productivity of employees. Noting the employee discipline is necessary because if the employee has been disciplined at work, the employee can be said to be productive.